The Relationship between the Implementation of Pregnancy Exercise and the Smooth Delivery Process and Perineal Rupture at PMB Alberta Angin B. 2022 - Rosa Marya; Jasmawati; Rivan Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between pregnancy exercise and the smooth delivery process and perineal rupture at PMB Alberta Angin B. The type of this research was Quasi Experiment with an analytic descriptive research design. The population in this study were all pregnant women who had done pregnancy exercise more than 3 times, namely 20 respondents and 17 respondents as the sample. Sampling using non-probability sampling method with purposive sampling technique. The data analysis technique used Fisher's exact test to determine the relationship between variables. The results of the hypothesis test found that there was an effect of pregnancy exercise on the process of smooth delivery and perineal rupture at PMB Alberta Angin B with a p-value of 0.028. So it can be concluded that there is a relationship between pregnancy exercise and the smooth delivery process and perineal rupture.